Effect of Oxidation Temperature and Chlorine Source on the Gate Oxidation Process for High Power IGBT - ZHANG Quan; LIU Guoyou; HUANG Jianwei (Kongzhi Yu Xinxi Jishu)
Two main gate oxidation processes of high power IGBT based on dry oxidation and wet oxidation were studied by capacitance-voltage (C-V) method. Effect of oxidation temperature and chlorine source on the quality of gate oxidation, especially on fixed oxide charge (Nss) and interface trapped charge (Dit), was investigated in detail. Experimental results show, for dry oxide grown in 1 000℃ ~ 1 150℃ without chlorine source, lower fixed oxide charge was obtained by high-temperature nitrogen annealing and the effect of oxidation temperature on Nss could be ignored nearly. However, chlorine obviously increased Nss of dry oxide when oxidation temperature increased above 1 050℃ . Interface trapped charge of dry oxide was easy to be controlled at low level by 450℃ hydrogen-containing postmetal anneal, which clearly decreased the effect of oxidation temperature and chlorine source on Dit. For wet oxide grown in 850 ~1 000 ℃, it was difficult to obtain lower Nss and Dit by both high-temperature nitrogen annealing and 450 ℃ hydrogen-containing post-metal anneal. Compared to dry oxidation, wet oxidation significantly increased the dependence of Nss and Dit on oxidation temperature and chlorine source.